International Treaties In the Czech Legal Order. - Zeman, Ondřej; Trávníčková, Zuzana, 1977-; Sladký, Pavel; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2007)
In the second, common part describes public international law and it's relation to the national law. Subsequently the system of sources of public international law and application of the international treaties to the system of the national law. In the third, analytical part describes relationship between international and the Czech law, it's historical development and present situation and the relation of the Czech national law to the acquis communautaire as well.
Vedoucí práce: Zuzana Trávníčková
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2009
Rok obhajoby 2009
Keywords: podnikání a právo [obor dipl. práce]; diplomové práce; master's theses